2019
DOI: 10.1021/acsami.9b15286
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Redox Range of Surface-Immobilized Metallocomplexes Using Molecular Interfaces

Abstract: Rationally designed material interfaces offer opportunities to control matter and energy across multiple length scales, yet remain challenging to synthetically prepare. Inspired by nature, where amino acid residues and softmaterial coordination environments regulate the midpoint potentials of metals in proteins, thin-film polymeric coatings have been developed to assemble molecular components, including catalysts, onto solid-state (semi)conducting surfaces. In this report, we describe the immobilization of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 54 publications
(71 reference statements)
1
28
0
Order By: Relevance
“…In general, this vibrational mode is sensitive to both the elemental nature of the porphyrin metal center and its local coordination environment [61–64] . For these reasons, in‐plane porphyrin deformation vibrations have been used as diagnostic signals for indicating the presence of metalloporphyrins on surfaces and gaining information on their local chemical environments [25,60,65–68] . In this report, the difference in ν Fe‐N frequencies of [FeTTP]Cl and [Fe 2 FP]Cl 2 suggests the fused complex provides a more rigid ligand motif.…”
Section: Figurementioning
confidence: 81%
“…In general, this vibrational mode is sensitive to both the elemental nature of the porphyrin metal center and its local coordination environment [61–64] . For these reasons, in‐plane porphyrin deformation vibrations have been used as diagnostic signals for indicating the presence of metalloporphyrins on surfaces and gaining information on their local chemical environments [25,60,65–68] . In this report, the difference in ν Fe‐N frequencies of [FeTTP]Cl and [Fe 2 FP]Cl 2 suggests the fused complex provides a more rigid ligand motif.…”
Section: Figurementioning
confidence: 81%
“…A previously established sol−gel route for producing highly mesoporous ATO coatings was adapted for the fabrication of macroporous ATO coatings [26,38,40,45,46]. Briefly, a clear solution with 1.00 g of SnCl 4 •5H 2 O (Alfa Aesar, 98%) (Haverhill, MA, USA) and 0.05 g of SbCl 3 (Alfa Aesar, ≥99.9%) in 6.50 g of n-BuOH and 1.0 g of deionized water was prepared and cooled to about 4 • C in ice bath, and then transferred into an Ultra-Turrax tube drive with a rotor stator element.…”
Section: Preparation Of Ato Film On Fto Glassmentioning
confidence: 99%
“…We previously demonstrated that wild type (WT) cyt c could be absorbed in thin films of highly mesoporous ATO with retention of its native structure and redox properties [36]. Moreover, cobalt porphyrins have been previously interfaced with TCOs and other semiconductors [37][38][39]. The immobilization strategy for binding cyt c to ATO takes advantage of the electrostatic interaction between substantial negative charges on the metal oxide surface and the protein's positively charged surface, mediated by lysine residues [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, we herein report the design and catalytic HER features of three water‐soluble polymers with appending Co porphyrin units and different side‐chain groups (Figure ). Polymers have been reported to enhance electrocatalysis and photocatalysis recently . Apart from significantly improved water solubility, porphyrin units are protected by polymer chains to avoid their degradation via oxidative oligomerization .…”
Section: Figurementioning
confidence: 99%